Pemberdayaan Pemuda Karang Taruna Kedoya Selatan, Jakarta Barat melalui Pelatihan Upcycle Limbah Kayu Peti Kemas menjadi Lampu Meja - Awang Eka Novia Rizali; Ariani Ariani; Elda Franzia Jasjfi; Layla Nurina Kartika Iskandar (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Karang Taruna youth in RT 10 RW 005, Kedoya Selatan Village, Kebon Jeruk Subdistrict, West Jakarta have the potential and motivation to work, but they do not yet have adequate access to skills development oriented towards economic capacity building. One relevant opportunity for empowering Karang Taruna youth today is to process wood waste into products of economic value through upcycling. In their residential area, there is a significant amount of waste wood from used shipping containers available, but its utilization has not been optimized. Based on these conditions, the Community Service (PkM) team of the Faculty of Art and Design (FSRD) Universitas Trisakti held a training session on processing waste wood from shipping containers into table lamps using upcycling techniques. The participatory action research (PAR) method was applied in this training, which was attended by 10 participants, accompanied by guidance from the instructors. The training resulted in 10 functional and marketable table lamps. Based on the evaluation results, minor obstacles were identified, with 3% of all participants stating that they still had difficulties with assembly and 2% experiencing obstacles with electrical installation.